2016
DOI: 10.1371/journal.pone.0161099
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequences of Three Apple chlorotic leaf spot virus Isolates from Hawthorns in China

Abstract: The genome sequences of Apple chlorotic leaf spot virus (ACLSV) isolates from three accessions of hawthorns (Crataegus pinnatifida) grown at Shenyang Agricultural University were determined using Illumina RNA-seq. To confirm the assembly data from the de novo sequencing, two ACLSV genomic sequences (SY01 and SY02) were sequenced using the Sanger method. The SY01 and SY02 sequences obtained with the Sanger method showed 99.5% and 99.7% nucleotide identity with the transcriptome data, respectively. The genome se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Complete genome nucleotide sequences of 13 ACLSV isolates have been previously published, including isolates P205, A4, MO-5 from apple and B6 from apple and hawthorn (Sato et al 1993;Yaegashi et al 2007;Guo et al 2016), P863 and PBM1 from plum (German et al 1990;Jelkmann 1996) and Ta Tao 5, Z1 and Z3 from peach (Marini et al 2008;Niu et al 2012). Based on amino acid sequences, Japanese ACLSV CPs were reported to cluster into types P205 and B6, according to covariation of two combinations of five highly conserved aa sets: Ala 40 , Val 59 , Phe 75 , Ser 130 and Met 184 for isolates P205 and A4, and Ser 40 , Leu 59 , Tyr 75 , Thr 130 and Leu 184 for isolates B6 and MO-5 (Yaegashi et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Complete genome nucleotide sequences of 13 ACLSV isolates have been previously published, including isolates P205, A4, MO-5 from apple and B6 from apple and hawthorn (Sato et al 1993;Yaegashi et al 2007;Guo et al 2016), P863 and PBM1 from plum (German et al 1990;Jelkmann 1996) and Ta Tao 5, Z1 and Z3 from peach (Marini et al 2008;Niu et al 2012). Based on amino acid sequences, Japanese ACLSV CPs were reported to cluster into types P205 and B6, according to covariation of two combinations of five highly conserved aa sets: Ala 40 , Val 59 , Phe 75 , Ser 130 and Met 184 for isolates P205 and A4, and Ser 40 , Leu 59 , Tyr 75 , Thr 130 and Leu 184 for isolates B6 and MO-5 (Yaegashi et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…While previous studies have focused primarily on sequencing of full-length ACLSV genome [10,11,77,78], in this study, locus-derived mdm-miRNAs were identified from the apple genome that directly bind to multiple consensuses genomic regions of ACLSV. Further, no previous report has shown that apple mdm-miRNAs bind to ACLSV, predicting several, functionally related, host-miRNA-virus-mRNA interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The ACLSV genome is 74.7-7.56 kbp in size, not including the poly-A tail and the 3 -and 5 -untranslated regions. The genome encodes three overlapping open reading frames (ORFs) from which the viral replication-associated protein (Rep), movement protein (MP), and coat protein (CP) are encoded [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…ACLSV is the type species of the genus Trichovirus , and has a single-stranded positive sense RNA genome of 7,474–7,561 nucleotides excluding the poly(A) tail ( German et al, 1990 ; Guo et al, 2016 ; Sato et al, 1993 ). The genomic RNA consists of 3 open reading frames (ORFs); ORF1 encodes the replication-associated protein, ORF2 the 50 kDa movement protein, and ORF3 the coat protein.…”
mentioning
confidence: 99%
“…2 ). There is considerable diversity between isolates of ACLSV from different regions and hosts (e. g., Al Rwahnih et al, 2004 ; Katsiani et al, 2014 ), ranging from 67.2–90.2% full genome nucleotide identity ( Guo et al, 2016 ; Niu et al, 2012 ). Based on the observed sequence identities and trade practices, we suggest that ACLSV-GW may be derived from apple graft-propagated material originally cultured in Japan.…”
mentioning
confidence: 99%